Navigating VUCA: Strategic leadership competencies among university administrators in Malaysia during the COVID-19 pandemic - Abu Hassan, Mahadi; Kudus, Norliah; Mohamed, Shahrulanuar; Abdullah, Fauziah; Mohd Noor, Ahmad Ridzwan (Human Resource Management Academic Research Society, 2024)
The COVID-19 pandemic has precipitated an unprecedented crisis, exposing higher education institutions worldwide to a volatile, uncertain, complex, and ambiguous (VUCA) environment. In Malaysia, university professional administrators were thrust into leading their institutions through these turbulent times, requiring the rapid adoption and deployment of strategic leadership competencies. This paper examines the key competencies of strategic leadership demonstrated by university administrators in Malaysia to effectively navigate the challenges of the VUCA environment during the pandemic. Through a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, this study synthesizes relevant research published between 2020 and 2023. The review covered three key academic databases: Scopus, Web of Science, and Google Scholar, using search terms such as "strategic leadership," "competencies," "higher education," "VUCA," and "COVID-19." The findings reveal critical competencies including adaptability, strategic thinking, crisis management, effective communication, and emotional intelligence, all of which were pivotal in enabling administrators to manage the abrupt transition to remote learning, safeguard the well-being of staff and students, and maintain academic continuity amidst widespread uncertainty. Furthermore, the study highlights the importance of collaboration, innovation, and ethical decision-making as core competencies that facilitated resilience and sustainability in the face of complex and rapidly evolving challenges. These insights emphasize the need for sustained professional development and capacity-building to enhance leadership effectiveness in Malaysia’s higher education sector and provide valuable implications for university administrators worldwide in preparing for future crises.